Institutionalising guideline development in a new universal healthcare system: a study in Cyprus - Kolokotroni, Ourania; McGuire, H.; Kyriakou, M.; Kouis, P.; Sioftanos, A; Yiallourou, A.; Achilleos, H.; Yiallouros, P.; Nikolopoulos, G. (My University, 2024)
Guideline development is a lengthy and diligent process that involves the assessment and interpretation of evidence by a committee. Whilst the implementation of high quality healthcare guidelines ensures consistency and quality in healthcare delivery, many countries worldwide, including Cyprus, lack the capacity and resources to develop de novo guidelines.
Keywords: consultation; quality of care